THE USE OF TECHNOLOGY IN ENHANCING LEARNING OUTCOMES IN ISLAMIC EDUCATION: A REVIEW OF THE LITERATURE - Zulpikar Zulpikar (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
The use of technology in education has become a popular trend in recent years, and Islamic education is no exception. This paper reviews the literature on the use of technology in enhancing learning outcomes in Islamic education. The review focuses on studies that have investigated the impact of technology on students' knowledge, attitudes, and skills in Islamic education. The findings suggest that technology can be a valuable tool in enhancing learning outcomes in Islamic education, particularly when used to supplement traditional teaching methods. However, the effectiveness of technology is dependent on various factors, including the type of technology used, the quality of instruction, and the level of student engagement.